THE ROLE OF FRANCHISES IN THE CONSOLIDATION OF THE CENTRALITY OF MEDIUM SIZED CITIES: THE CASE OF SAO JOSE DO RIO PRETO-SP - Engel, Priscila Estevam [UNESP] (Univ Federal Ceara, Programa Pos-graduacao & Filosofia, 2015)
Medium cities have gone through a restructuring process and this can be seen significant changes in its urban structure, such as the deployment of commercial establishments that follow the logic of franchise systems, which prioritize settle in large avenues, and centers mostly in shopping Centers. Este work seeks to understand the consumer and their effects in space and content of the medium-sized cities, especially Sao Jose do Rio Preto located in the northwestern portion of the State of Sao Paulo, and the interactions socioespais as the background. Thus, we propose to analyze the logical location of franchises in intra and inter space of this city, since such companies appropriated to specific spatial conditions to ensure the success of the brand and the sale of its products, a fact that reveals the territorial logic that is inherent.
Keywords: Middle Cities; Franchising; Shopping Mall; Networks